On the coding rate for differential modulation and detections - Ya-chong XU; Dong-wei HU (网络与信息安全学报)
Differential demodulation is an important method of solving the information transmission which is used in the high dynamic condition of the wireless communication.The coding rate for differential modulation and detec-tions neither be too high,nor be too low.To find the optimal coding rate,the Shannon limit of error free transmis-sions with different rates for differential BPSK and differential QPSK were derived.Thereafter,the optimal coding rate was obtained from the view point of information theory.Convolutional codes and Turbo codes with different rates were employed,and simulations were conducted for the verification of the result.